Ethnicity, education attainment, media exposure, and prenatal care in Vietnam. Issue 1 (2nd January 2017) - Trinh, Ha Ngoc; Korinek, Kim
ABSTRACT: Objective. Prenatal care coverage in Vietnam has been improving, but ethnic minority women still lag behind in receiving adequate level and type of care. This paper examines ethnic disparities in prenatal care utilization by comparing two groups of ethnic minority and majority women. Design. We examine the roots of ethnic disparity in prenatal care utilization, focusing on how education and media exposure change health behaviours and lessen disparities. We rely on the 2002 Vietnam Demographic and Health Survey to draw our sample, predictors and the three dimensions of prenatal care, including timing of onset, frequency of visits, and type of provider. Results. Results from multinomial-, and binary-logistic regression provide evidence that ethnic minority women are less likely to obtain frequent prenatal care and seek care from professional providers than their majority counterparts. However, we find that ethnic minority women are more likely to obtain early care compared to ethnic majority women. Results for predicted probabilities suggest that education and media exposure positively influenced prenatal care behaviours with higher level of education and media exposure associating with accelerated probability of meeting prenatal care requirements. Conclusion. Our results imply the needs for expansion of media access and schools as well as positive health messages being broadcasted in culturally competent ways.